ERIN GRUWELL'S EFFORT TO BE A GOOD TEACHER INRICHARD LAGRAVENESE'S FREEDOM WRITER 2007: ANINDIVIDUAL PSYCHOLOGICAL APPROACH - RETNOWANTI, RETNOWANTI (2011)
This study is to reveal Erin's effort reflected in Freedom Writer movie directed by Richard Lagravenese published in 2010. The objective of the study is to analyze the structural elements in the movie and to analyze the effort based on Individual Psychological approach. The object of the study is the movie Freedom Writers directed by Kenny Leon. The researcher employs the descriptive qualitative research as a type of the research. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the movie and script of Freedom Writers and the secondary data source is information related to the primary data source, and website. The method of collecting data is observation and library review. The method of analyzing data is descriptive technique. Based on the analysis, the researcher draws two conclusions: first, based on the structural analysis, Richard Lagravenese wants to deliver a message that a teacher shall be a creative person. Second, based on the individual psychological analysis, it shows that the teacher shall work hard to achieve noble dreams.